Recent advances in operator algebras collection of talks - Conference on Operator Algebras; Conference on operator algebras Orleans, USA Jul-92 (Paris Societe Mathematique de France, 1995)
This volume gathers contributions from participants of Operator algebras, Orl ns-July 1992, a satellite conference of the First European Congress of Mathematics. It presents some important developments in the following subjects: quantum groups in their C*- algebraic version, free probability theory, operator algebras associated with groups, classification of von Neumann factors, K-theory of C*- algebras and operator spaces.
Keywords: Operator algebras